Shortages and the informal economy in the Soviet republics, 1965–892. (12th April 2017) - Kim, Byung‐Yeon; Shida, Yoshisada
Abstract: This study measures the informal economy and shortages of consumer goods in the Soviet republics from 1965 to 1989 to estimate the relationships between these two variables. Using estimation methods, including a fixed‐effect model and the instrumental variable approach, we find that the informal economy and shortages reinforced each other. Results indicate that the Soviet central planning system was difficult to sustain. Substantial heterogeneities across the Soviet republics exist not only in the extent of the informal economy and shortages, but also in the associations between the two variables.